Effect of Synthesis Methods on Properties of Copper Oxide Doped Titanium Dioxide Photocatalyst in Dye Photodegradation of Rhodamine B - Cheng Yee Leong; Hao Lin Teh; Man Ching Chen; Siew Ling Lee (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Copper modified titanium dioxide photocatalysts have been widely reported for their excellent performance in the wastewater treatment. However, there is lack of information on the effect of different synthesis methods towards the properties and catalytic activity of the photocatalyst. In this research, a series of copper-doped titanium dioxide (Cu-TiO2) photocatalysts were synthesized via three different methods of sonochemical, impregnation and physical mixing. Cu-TiO2 with varied molar ratios of Cu dopant to TiO2 TR595 (100:0, 99:1, 98:2, 97:3 and 96:4) were prepared. Comparison of physical-chemical properties and photocatalytic activity among the synthesized samples were made. X-ray diffraction analysis depicted the formation of TiO2 rutile phase in all samples. Besides, diffuse reflectance UV-visible analysis proved that the synthesized samples were active under visible light region. According to the Tauc plot and photoluminescence spectra, the band gap energies and recombination rate of electron-hole pairs of Cu-TiO2 samples decreased upon loading of Cu. Moreover, EDX analysis confirmed the existence of Ti and Cu in all the samples. The photocatalytic efficiencies of the synthesized samples were discovered through photodegradation of Rhodamine B organic dye under 6 hours of visible light irradiation. Amongst, Cu-TiO2 photocatalysts synthesized via sonochemical method with molar ratio of 98:2 produced the highest photocatalytic activity of 64.8% which attributed to the lowest recombination rate of photogenerated charge carriers and availability of large number of reactive oxidative species.